Analisis Rantai Pasok dan Profit Margin Ternak Kambing di Kabupaten Banyumas - Eskatectona, Aulia Desta; Hidayat, Nunung Noor; Mastuti, Sri (ANGON: Journal of Animal Science and Technology, 2021)
Background. This research aims to cognize the supply chain of goat farms in Banyumas Regency, to analyze the profit margins achieved by goat livestock marketing agencies in Banyumas Regency and to focus the factors that affect the profit margins of goat livestock in Banyumas Regency. Materials and methods. The sampling method was carried out by survey method, conducting interviews using a questionnairespecifically. The technique of determining the area sample was carried out by using purposive sampling method, namely two animal markets in Banyumas Regency were selected, namely the Sokaraja Animal Market and the Cilongok Animal Market. The sampling technique was carried out by the Snowball Sampling method in order to obtain a sample of 30 respondents. The variables studied were the dependent variable is profit margin and the independent variable are the the price of livestock, length of goats raising, level of education and level of traders. The supply chain distribution of goats was analyzed descriptively, the amount of profit margin of each institution was analyzed using Net Profit Margin (NPM) analysis, and the influence of economy social factors was analyzed using multiple linear regression. Results. The results of this research are first, there are 3 patterns of supply chain in the goat farms business in Banyumas Regency, namely the supply chain pattern I (breeders, merchants I, consumers or butchers), supply chain pattern II (breeders, merchants I, merchantsII, consumers or butchers) and pattern Supply chain III (breeders, merchants I, merchants II, merchants III, consumers or butchers); second, the profit margin achieved by merchants I and merchants II of goat livestock in Banyumas Regency has a difference thing where the value of the profit margin for merchantsI is 15% meanwhile another one was 6.54%; third, profit margin was obtained by the price of livestock, length of raising and the level of merchants. Conclusion. Traders should sell goat livestock without going through the supply chain too much and sell at the time of Eid al-Adha so that the profit margin generated is high.